ANALISIS DAN PERHITUNGAN EFISIENSI DAYA PEMBANGKIT LISTRIK TENAGA MIKROHIDRO DENGAN TURBIN JENIS FRANCIS MENDATAR - Edeline Melati Dewi (2023)
Micro hydro power plants are small to medium scale power plants where the main source is an alternative energy in the form of pressurized water. This micro-hydro power plant or PLTMH has several very important components, namely a turbine and a generator. The PLTMH in Sindangcai uses a Francis type turbine. The purpose of this study is to determine the efficiency of a micro-hydro power plant in Sindangcai. This study will use head, discharge, output power as variables to determine the maximum efficiency of the Sindangcai PLTMH. Measurements were made at 13 different water level points, namely the highest part of 1.27 m with a resulting discharge of 3.5052 m3/s and the shallowest part of 0.7m with a resulting discharge of 1.932 m3/s. The results of the study show that the highest efficiency obtained is 85,9% with the power generated at 1.374,03 KW. And the smallest efficiency obtained is 47,3% with the resulting output power of 757.344 KW.